Synaptic and Fast Switching Memristance in Porous Silicon-Based Structures - Torres-Costa V; Mäkilä E; Granroth S; Kukk E; Salonen J (MDPI, 2022)
Memristors are two terminal electronic components whose conductance depends on the amount of charge that has flown across them over time. This dependence can be gradual, such as in synaptic memristors, or abrupt, as in resistive switching memristors. Either of these memory effects are very promising for the development of a whole new generation of electronic devices. For the successful implementation of practical memristors, however, the development of low cost industry compatible memristive materials is required. Here the memristive properties of differently processed porous silicon structures are presented, which are suitable for different applications. Electrical characterization and SPICE simulations show that laser-carbonized porous silicon shows a strong synaptic memristive behavior influenced by defect diffusion, while wet-oxidized porous silicon has strong resistance switching properties, with switching ratios over 8000. Results show that practical memristors of either type can be achieved with porous silicon whose memristive properties can be adjusted by the proper material processing. Thus, porous silicon may play an important role for the successful realization of practical memristorics with cost-effective materials and processes.